Post-Colonial Nigerian State and Complexities of Irregular Cross-Border Migration - Obikaeze, Victor Chibuike; Iloh, Emeka C. (Journal of Contemporary International Relations and Diplomacy, 2023)
The post-colonial Nigerian state has been confronted with internal socio-economic and political quagmires. Over the years, the globally accepted standards for sustainable human capital development seem to have eluded the Nigerian citizens, thereby creating situations of reoccurring social complexities. Irregular migrations across Nigerian borders have implicated trans-national illegalities especially within West African region, and African continent in general. Today, there is a consensus among scholars that human migration across borders of Nigeria has remained an issue of national concern with far-reaching consequences. The study aims at examining how cross-border human migration had been orchestrated by internal contradictions, hence leading to unprecedented increase in organized trans-border illegal and criminal activities in Nigeria and beyond. The study adopts documentary method and employs the push and pull theory of migration that explains the phenomenon within analytical framework of trajectories of post-colonial Nigeria and complexities of cross border migration of Nigerians. The study argues that many migrants who chose irregular migration routes seemed not to be aware of the challenges they would encounter, neither are they sure of job opportunities in their destination countries, but due to years of governance failure in Nigeria, Nigerian migrants consider leaving the country as a better alternative. The paper further argues that no matter all measures put in place by Nigeria government and other West African states to prevent irregular migration, the possibility of achieving that is far from reality. As long as the Nigerian state remains irresponsible and irresponsive to economic hardships of its citizens, there will always be outflow of Nigerians who are ever willing to ‘escape’ from the abysmally poor living standards in the country.